A cost-effectiveness and budget impact analysis of apremilast in patients with psoriatic arthritis in Italy. (2nd April 2020) - Capri, Stefano; Migliore, A.; Loconsole, F.; Barbieri, Marco
Abstract: Aims: The aim of this study was to conduct a cost-effectiveness analysis, as well as a budget impact analysis, on the use of apremilast for the treatment of adult patients with psoriatic arthritis (PsA), within the Italian National Health Service (NHS). Methods: A Markov state transition cohort model, which was adapted to the Italian context, was used to compare the costs of the currently available treatments and of the patients' quality of life with two alternative treatment sequences, with or without apremilast as pre-biologic therapy. Moreover, a budget impact model was developed based on the population of patients treated for PsA in Italy, who can be eligible for treatment with apremilast. The eligible population was represented by adult patients with PsA who had an inadequate response to or were intolerant to previous disease-modifying antirheumatic drugs (DMARDs), for the approved indication, and for the treatment studied in the economic analytic model. Results: This cost-effectiveness analysis estimated that the strategy of using apremilast before biologic therapy is cost-effective, with an incremental cost-effectiveness ratio of €32, 263.00 per QALY gained which is slightly over the normal threshold found in other Italian economic studies, which usually considers a 40-year-period. Conversely, the budget impact analysis was conducted over 3 years, and it led to an estimated annual saving of €1.6 million, €4.6 million and €5.5 million in the first, second and third year of apremilast commercialization, respectively, for a total saving of €11.75 million in 3 years. Limitations: Limitations of this analysis include the absence of head-to-head trials comparing therapies included in the economic model, the lack of comparative long-term data on treatment efficacy, and the assumption of complete independence between the considered response rates to therapy. Conclusion: The use of apremilast as a first option before the use of biologic agents may represent a cost-effective treatment strategy for patients with PsA who fail to respond to, or are intolerant to, previous DMARD therapy. In addition, based on a budget impact perspective, the use of apremilast may lead to cost savings to the Italian healthcare system.